MANTRA DANGDAN BANJARSARI: CERMIN KONSEP CANTIK ORANG SUNDA DI BANJARSARI - Afidah, Nuri Novianti (2012)
The research was motivated by the belief of common people in Banjarsari that the spirits of ancestors will help them to achieve their wish with the use of a variety of mantra dangdan. Four main difficulteis that were faced during the studies are, (1) different types of lingual MDB, (2) describing some of the words used in MDB, especially those refer to parts of body realted to beauty of a lady (3) the mantra dangdan used contains concepts of beauty among Sundanese people in Benjarsari and (4) classification of MDB.This research is a descriptive study of the mantra dangdan Banjarsari (MDB) which explains the concept of beauty among Sundanese people in Banjarsari. The study was conducted through a linguistic anthropological approach, which examines language, in this case spells of dangdan in the socio-cultural context. The data studied are different types of MDB in the form of text and verbal language collected by listening to speakers of mantra. Data collection techniques used in this study include participant observation, periodic observations to the field, and in-depth interviews. Techniques of data analysis begins by collecting data, doing transcription followed by a free translation, analysis and classification based on context, analyzing the form (structure) and function of language used in mantra dangdan Banjarsari, and interpret the mindset or view of speakers who use dangdan Banjarsari to gain beauty. The data is sourced from the five respondents who were the speakers of the spell, one Nyi Ronggeng, three elders, and one additional respondent as former speaker of mantra. In the final stage, the researcher was able to make conclusions of what has been described in previous analyzes.Here are the results of research that can be described briefly. First, the various forms of MDB lingual outlines include words and phrases. Second, variations in the MDB reference lexicon consists of (1) the petition, (2) the body, (3) animals, (4) object, (5) eye activity, (6) circumstances, (7) relationships, and (8) expectations. Third, the concept and the sentences used in the MDB reflects beauty in Sundanese people in Banjarsari. The data shows that there are seven sentences that reflect the concept of Sundanese beauty and some lexicon such as Raray (face), lenggik (slim), and sieup (sweet / content) are more frequent and dominant than other lexicon. Fourth, in terms of classification, MDB is divided into several categories, namely categories of places, categories of activities, actors category and frequency category.